Expanded use of transconjunctival orbitotomy in management of different orbital tumors at different locations. Issue 5 (September 2021) - Mohammad, Ahmad A; Abo-Ghadir, Ahmed A; Othman, Ihab S; Abdel-Radi, Mahmoud; Mohammad, Abd El-Nasser A
Purpose: To assess the surgical outcomes of transconjunctival approach in management of different orbital tumors at different locations. Methods: This prospective, non-comparative, clinical interventional study was conducted in the period between March 2017 and January 2020 and included 61 patients with histologically proved orbital tumors. In all cases, a conjunctival incision near the fornix was made depending on the tumor location as revealed by CT or MRI. A traction suture was applied to one or two relevant recti muscles to guide the globe toward the desired direction. Blunt orbital dissection was made toward the tumor until exposing its anterior surface. The procedure was considered successful if the predetermined decision (total excision with improved clinical manifestations for benign and biopsy for diagnosis in malignant tumors) was achieved without causing permanent complications. The procedure was considered a failure if the predetermined decision was not achieved or if permanent complications developed. Results: The patients were divided into: Group A of 47 patients (77.05%) with benign tumors and Group B of 14 patients (22.95%) with malignant tumors. The overall success rate of the approach was 98.36% (60 out of 61 patients), while failure occurred in one case (1.64%). Conclusions: The transconjunctival orbitotomy is an excellent approach to manage different tumors at different orbital locations with rapid recovery and maximum cosmetic results. It is the only approach that can access intra-conal, mid-orbital tumors whatever their relation to the optic nerve without crossing it.